From Likes to Sales: Analyzing Opportunities and Emerging Trends in TikTok Live Shopping for Retailers - Garry Ashley Bray (Law and Economy, 2023)
This paper explores the transformative impact of TikTok Live Shopping on the landscape of retail in the United States, analyzing opportunities, challenges, and consumer behavior trends over the next five years. Delving into the fusion of entertainment and commerce on TikTok, the study investigates the potential benefits for retailers leveraging this dynamic platform. Current trends and future projections, informed by real-world examples and expert analyses, provide a roadmap for retailers aiming to thrive in the evolving TikTok Live Shopping ecosystem. Additionally, the paper addresses challenges such as technological learning curves, regulatory considerations, and content production hurdles, proposing strategic solutions to navigate these obstacles. A deep dive into consumer behavior on TikTok unveils unique aspects influencing purchasing decisions during live shopping events, exploring psychological nuances that drive engagement and conversion. In conclusion, the paper offers actionable recommendations for retailers to strategically position themselves for success in the dynamic realm of TikTok Live Shopping.